The Relationship between Amanatul Ummah Islamic Boarding School and Local Community’s Religiosity - Chalim, Asep Saifuddin (Universitas Negeri Malang, 2017)
Abstracts: Many studies conducted by prominent scholars found that Islamic boarding school in Indonesia have been playing its roles not only in religious and education matter but also in the other areas, such as social, economic and environment. This study sought to analyze the impact of the presence of Islamic boarding school on the religiosity of surrounding Muslim communities the object of the study is households who live in seven villages surrounding the Islamic boarding school Amanatul Ummah, Mojokerto regency, East Java Province, Indonesia. To measure the level of Muslim religiosity, the study used the value of the Five Pillars of Islam dimensions based on the 5-point Likert Scale. By comparing the average value of religiosity of each dimension, it can be drawn a conclusion whether there is a significant positive impact or not. The study found that the average value of Muslim religiosity after the presence of an Islamic boarding school is greater than that before. These findings show that the presence of an Islamic boarding school has a significant positive impact on the surrounding Muslim religiosity. Moreover, the study observes that Islamic boarding school has been practicing a moderate way in Islamic religious proselytizing that makes surrounding communities feel comfortable to adapt and change.Keywords: the Five Pillars of Islam, Islamic boarding school, moderate teaching, religiosityAbstrak: Beberapa penelitian yang dilakukan para ahli menemukan bahwa pondok-pondok pesantren di Indonesia telah memainkan perannya tidak hanya dalam persoalan agama dan pendidikan, tetapi juga bidang lain, seperti masalah sosial, ekonomi, dan lingkungan. Penelitian ini bertujuan untuk menganalisis dampak keberadaan pondok pesantren tingkat religiusitas masyarakat Muslim di sekitarnya. Sasaran penelitian ini adalah rumah-tangga yang berada di 7 desa di sekitar pondok pesantren Amanatul Ummah, Kabupaten Mojokerto, Provinsi Jawa Timur. Untuk mengukur tingkat religiusitas kaum Muslim, penelitian ini menggunakan the Value of the Five Pillars of Islam Dimensions berdasarkan pada Skala Likert dengan rentang 5 poin (the 5-point Likert Scale). Dengan membandingkan rata-rata nilai tingkat religiusitas setiap dimensi (the average value of each dimension) sebelum dan sesudah keberadaan pondok pesantren, kita dapat menarik sebuah konklusi apakah ada dampak positif atau tidak. Penelitian ini menghasilkan temuan bahwa rata-rata nilai dari religiusitas Muslim sesudah keberadaan pondok pesantren adalah lebih besar dibandingkan dengan sebelumnya. Dengan demikian, temuan ini menunjukkan bahwa keberadaan pondok pesantren mempunyai dampak positif yang signifikan terhadap religiusitas masyarakat Muslim di sekitarnya. Penelitian ini lebih lanjut telah mengamati dan mendapatkan kenyataan bahwa pondok pesantren telah mempraktikkan dakwah agama Islam dengan cara moderat yang membuat masyarakat di sekitarnya merasa nyaman untuk beradaptasi, mengadopsi dan berubah.Kata kunci: the Five Pillars of Islam, moderate way, pondok pesantren, religiosity